Regulated Emergence of the African swine fever virus: B646L (p72) Gene Based Bayesian Coalescent Analysis: Life Sciences-Microbiology - S. Patil, Sharanagouda; Venkataravana, Prabhakarareddy Anapalli; SR, Santosh Kumar; Suresh., Kuralayanapalya Puttahonnappa; Indrabalan, Uma Bharathi; Sridevi, Rajangam; Jayappa, Veeresh Santhebennur; Srinivasa, Siddappa B. Kakkalameli5, Chandrashekar; Kollur, Shiva Prasad; Shivamallu, Chandan (International Journal of Life Science and Pharma Research, 2021)
African swine fever virus (ASFV) belongs to the genus of virus of the Asfaviridae family. ASFV infection causes hemorrhage and high death rate hence increased loss to the swine community. It is a complex infectious disease of swine, which constitutes devastating impacts on animal health and the economy of the pig farmers. It has been confirmed that virus infections has been spreading in swine population for many years. In this study, the evolutionary epidemiology analysis of ASF virus from the geographical regions Africa, Europe, and Asia, respectively were retrieved from GenBank for the analysis. The nucleotide gene sequences of the viral protein p72 encoded by B646L gene published during 1960-2020 was taken in to study. The Bayesian skyline model with uncorrelated randomized clock model was employed to reconstruct the evolutionary history of the virus, to identify virus population demographics. Results of the analysis suggested that ASFV exhibited a high evolutionary rate, as the divergence caused reduction in the population in the recent years. The B646L gene of ASFV had an evolutionary rate of 4.13 X 10-6 substitution/site/year and the tMRCA as 3.15 x 105 with 95 percent HPD range in years (2.4 x 104 to 1.23 x 106) was obtained. In conclusion, the evolutionary study of ASFV with p72 protein from the ASFV of the B646L genes indicated that they evolved at a faster rate and plays a major role in the evolutionary process. Further, this study may help in designing or developing vaccines to control the spread of the disease.